Pengaruh Kualitas Udara di Tempat Kerja terhadap Kesehatan dan Produktivitas Pekerja - Irma Fajriah (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
This study reviews the impact of workplace air quality on employee health and productivity. Poor air quality in work environments is linked to various health issues, including respiratory diseases, fatigue, and decreased concentration, which subsequently affect work efficiency. The review explores existing studies on air pollution exposure, workplace ventilation, and their effects on employee performance. It also highlights mitigation strategies such as air filtration systems and proper ventilation to improve workplace conditions. The findings suggest that improving air quality can significantly enhance employee well-being and productivity.